Characteristic Quantity Analysis of Single-Phase Contact Tree Ground Fault of Distribution Network Overhead Lines - Jianbo He; Yao Zhou; Yilin Li; Guangqing Zhang; Jiayu Liang; Hao Shang; Wenjun Ning (Energies, 2023)
When the overhead line passes through the forest area, the conductor may contact the line to induce the tree-contact single-phase-to-ground fault (TSF), and the persistence of TSF may induce wildfires, bringing serious consequences. However, the amount of TSF electrical features is weak, and traditional protection devices cannot operate effectively, so it is urgent to obtain typical characteristics of TSF. In this study, the simulation experiment is carried out for the tree-contact single-phase-to-ground fault. Firstly, the relativity between fault and characteristics like zero-sequence voltage, zero-sequence current, and differential current are analyzed theoretically. Then, the simulation experiment platform of TSF is built, and the time-varying fault characteristics are acquired. The experimental results show that the average value of the zero-sequence voltage, the amplitude of the power-frequency component of the zero-sequence current, and the amplitude of the power-frequency component of the first and end differential current can accurately reflect the fault current development trend of the single-phase contact tree fault of the conductor, and can be used as the typical characteristic quantity of TSF. The results of this study are helpful for further understanding the fault characteristics of TSF and provide theoretical support for the identification and protection design of TSF.